NATIONAL INNOVATION SPACE IN THE KNOWLEDGE ECONOMY - N. P. Krasochenkova (Real Economics Publishing House, 2016)
The features of the knowledge economy and knowledge fundamental role in the formation of the national innovation space are analyzed; economic function of knowledge, institutional mechanisms for the production of knowledge are revealed. Factors and areas that affect the creation of new knowledge are characterized. Organizing mechanism of interaction of the national innovation system subjects is grounded and presented.